ANALISIS PERILAKU KONSUMEN TERHADAP KEPUTUSAN MEMILIH BELANJA DI TOKO MODERN INDOMARET STUDI KASUS PADA MAHASISWA UNIVERSITAS BALIKPAPAN - wiwik saraswati; Sriwandini Palango (Universitas Widyatama, 2025)
The purpose of this study was to determine the influence of Consumer Behavior on the Decision to Choose Shopping at Modern Indomaret Stores in Balikpapan. This study was conducted on Balikpapan University Students with unknown respondents. This research method uses quantitative methods. Data collection was done by distributing questionnaires directly. The data analysis technique used for the study was multiple linear analysis by conducting instrument tests, classical assumption tests and partial hypothesis tests (t-tests). The results of multiple linear regression analysis showed that culture, social, personal and psychological factors have a positive and significant influence on purchasing decisions, both partially and simultaneously.